Gebyar Khitan Toraja “Khitanan Massal dan Layanan Kesehatan Gratis” - Djunaedi, Djunaedi; Nursinah, Andi; Rante, Anshar; Pannyiwi, Rahmat (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Circumcision (circumcision) in Indonesian is known as circumcision or supit, which is a guideline for Islamic law for both men and women. Not only adherents of the Islamic religion perform circumcision, Jews, Christians and other religions now also practice circumcision because it is proven to provide health benefits. Circumcision or circumcision is a surgical procedure to remove the foreskin / prepuce / scalp of the penis. The purpose and benefits of this Mass Circumcision PkM is to reduce the risk of infection and even reduce the risk of penile cancer. Mass circumcising of Muslim children who are about to reach puberty in the Toraja area, Fulfilling the Prophet's Sunnah, Socializing the importance of maintaining health and cleanliness, Growing concern for others. The method used is Mass Circumcision using the smartklamp method and tubes that don't need stitches and bandages, so that the child can immediately do his activities as usual. The Klamp circumcision method was chosen because it is more comfortable for the child and has minimal pain and the participant/patient is circumcised without any complications from the circumcision procedure. It is hoped that the Circumcision PkM activities will go well according to the expectations of the community.